A broadband quad-stable energy harvester and its advantages over bi-stable harvester: Simulation and experiment verification. (1st February 2017) - Zhou, Zhiyong; Qin, Weiyang; Zhu, Pei
Abstract: This paper presents a novel quad-stable energy harvester (QEH) to harvest vibration energy. The QEH is composed of a piezoelectric bimorph cantilever beam with a tip magnet and three external fixed magnets. The potential energy of the QEH is derived, which has four potential wells and three low barriers. This implies that the QEH needs relatively lower excitation energy to cross the barriers than the bi-stable energy harvester (BEH). Simulations are carried out for the BEH and QEH at different levels of excitations. Results show that the QEH owns a smaller threshold and a wider range of frequencies for occurrence of snap-through than the BEH. Thus the QEH can give out a large output voltage. Corresponding experiments were performed for validation. The experimental results are in agreement with the simulations, which means that the QEH can improve the harvesting efficiency considerably. Highlights: The electromechanical equations are established to characterize the quad-stable energy harvester. The quad-stable configuration can easily attain snap-through oscillations. The quad-stable energy harvester has a wider effective frequency band and improves the harvesting efficiency dramatically compared with the traditional bi-stable energy harvester.